POLA ASUH ORANG TUA ASUH TERHADAP REMAJA DI PANTI SOSIAL BINA REMAJA (PSBR) RUMBAI KELURAHAN MERANTI PANDAK KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Delia Okpita; Aswandi Bahar; Jasfar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the dominant parenting patterns applied by foster parents to their teenagers in the Panti Sosial Bina Remaja (PSBR) Rumbai Kelurahan Meranti Pandak, Rumbai Pesisir District, Pekanbaru City. The formulation of the problem in this research is which dominant pattern applied by foster parent to adolescent in Panti Soial Bina Remaja (PSBR) of Rumbai Kelurahan Meranti Pandak, Rumbai Pesisir Kota Pekanbaru District? After the research is conducted, it is expected to provide benefits to increase knowledge regarding matters relating to the Patronage of Parents Parent Care to Teens, especially for researchers. This study will be useful for adolescents as a reference to know the pattern of foster parents foster. This research is descriptive with quantitative approach which aims to describe the result of research with numbers. The sampling technique used simple sample random sampling technique (simple random sampling). Technique of data retrieval in this research is by questionnaire, which amounts to 247 item statement. Data were obtained from 20 respondents for trial samples and 41 people for the research sample. After a questionnaire in the trial, there are 12 items of invalid statement, and the researcher discards all the items of the invalid statement. The result of data analysis shows that the parenting pattern of foster parent to teenagers of democratic parenting type is very good with an average percentage score of 94.5%. This means that foster parents are more dominant applying parenting pattern to adolescents with the kind of democratic parenting.Keyword: The Pattern of Foster, Parenting